2008
DOI: 10.17159/2078-516x/2008/v20i4a273
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic response to exercise as measured by cardiovascular variability

Abstract: Heart rate variability (HRV), blood pressure variability (BPV) and baroreceptor sensitivity (BRS) are often used as measures of autonomic activity, even though reported results are not always comparable or as expected. It is known that endurance athletes have lower average resting heart rates than non-exercising individuals. 33,50 However, other exercise-induced autonomic influences on cardiac control are far more controversial.Autonomic control via sympathetic and parasympathetic modulation of the heart has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Typically, it is assumed that the sympathetic and parasympathetic systems are complementary, and thus, it would be expected that as HF declines, LF (and SCRs) would increase; however, it has been found that fluctuations in the two bands might be on different time scales (Shaffer & Ginsberg, 2017), thereby temporally uncoupling the responses of the two measures. This intriguing pattern has also been reported after steady‐state exercise in healthy participants (Grant & Ker, 2008; Maud & Foster, 2006: p. 52; Povea et al., 2005), suggesting that the combination of sleep restriction and an emotional challenge induces an adaptive response to maintain a constant HR response across WR and SR conditions. This conjecture is also consistent with the decreased self‐reported fatigue when watching the sad film clip in the SR condition.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Typically, it is assumed that the sympathetic and parasympathetic systems are complementary, and thus, it would be expected that as HF declines, LF (and SCRs) would increase; however, it has been found that fluctuations in the two bands might be on different time scales (Shaffer & Ginsberg, 2017), thereby temporally uncoupling the responses of the two measures. This intriguing pattern has also been reported after steady‐state exercise in healthy participants (Grant & Ker, 2008; Maud & Foster, 2006: p. 52; Povea et al., 2005), suggesting that the combination of sleep restriction and an emotional challenge induces an adaptive response to maintain a constant HR response across WR and SR conditions. This conjecture is also consistent with the decreased self‐reported fatigue when watching the sad film clip in the SR condition.…”
Section: Discussionsupporting
confidence: 69%
“…This intriguing pattern has also been reported after steady-state exercise in healthy participants (Grant & Ker, 2008;Maud & Foster, 2006: p. 52;Povea et al, 2005), suggesting that the combination of sleep restriction and an emotional challenge induces an adaptive response to maintain a constant HR response across WR and SR conditions. This conjecture is also consistent with the decreased selfreported fatigue when watching the sad film clip in the SR condition.…”
Section: Discussionsupporting
confidence: 64%
“…Although regular or chronic aerobic exercise training increases parasympathetic/vagal modulation of HR with decreased sympathetic tone at rest after recovery (Grant et al., 2008; Michael et al., 2017; Sandercock et al., 2008; Stanley et al., 2013), parasympathetic regulation initially decreases within a few minutes to hours following acute exercise (Buchheit et al., 2007; Stanley et al., 2013). This is due to augmented sympathetic and metaboreflex stimulations that perturb cardiac vagal control (Stanley et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sleep, regular exercise training program improves cardiovascular autonomic balance by increasing parasympathetic tone with a concomitant decrease in sympathetic tone at rest after recovery (Abad et al., 2014; Billman, 2002; Grant et al., 2008; Grässler et al., 2021; Sandercock et al., 2008). However, cardiac parasympathetic activity is initially decreased within a few minutes to hours after acute exercise (Stanley et al., 2013), whereas cardiac parasympathetic/vagal activity can return to pre‐exercise levels within 24 to 72 hr or rebound above baseline levels (Grant et al., 2008;Michael et al., 2017; Stanley et al., 2013). The parasympathetic response during exercise and post‐exercise recovery of vagal cardiac modulation is influenced by exercise characteristics (intensity, duration, modality and timing), as well as age and fitness levels of individuals (Grant et al., 2008; Guerra et al., 2014; Michael et al., 2017; Stanley et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation